PEMODELAN BANGKITAN PERGERAKAN BERDASARKAN AKTIVITAS MANDATORY (SEKOLAH DAN BEKERJA) DARI KOMPLEK PERUMAHAN DI KABUPATEN ACEH BARAT - Murdani Murdani; Renni Anggraini; Muhammad Isya (Prodi Magister Teknik Sipil Unsyiah, 2020)
The Johan Pahlawan subdistrict is one of the subdistricts in West Aceh. This subdistrict is the center of all community activities compared to the sub-districts in West Aceh Regency. This is because there are many government offices, schools, and trade centers. So that community activities tend to move to this sub-district. The modeling of trip generation has been performed by individuals in one area that will be needed to know by studying a variety of relationships between the characters of movements and the environment of land use. This research aimed at achieving the modeling movements of generation based on activities in the housing of Caritas, Islamic Relief, and IOM in the subdistrict of Johan Pahlawan in West Aceh Regency by identifying the factors which have influenced the occurrence of movements to the workplace by dwellers of housing. The data were collected by surveys, questionnaires. In this study, there are five types of activity, two as main activity and three as an additional activity. they are obtained is school activity (mandatory), work activity (mandatory), the shuttle of children activity (maintenance), shuttle household affairs activity (maintenance), and social activity (maintenance). Based on the results of running from several variables there are 5 variables that meet the criteria of the model, the variables are a number of family members (X1), family income (X2), age (X8), travel distance (X10) and gender (X11). The best models are: Work Activity (Y1) = 0.988 + 0.169 X1 + 0.582 X2, School Activity (Y2) = 1.684 + 0.865 X2 + 0.387 X8, Social Activity (Y3) = 0.885 + 0.564 X2 + 0.334 X10, Shuttle of Children Activity (Y4) = 1.028 + 0.902 X8 + 0.557 X11 and Shuttle Household Affairs Activity (Y5) = 2.367 + 0.931 X1 + 0.858 X2.